The college devaluation crisis : market disruption, diminishing ROI, and an alternative future of learning - Wingard, Jason (Stanford Business Books, Stanford University Press, 2022)
"Employers are stepping in to innovate new approaches to training talent that increasingly operates independently of the higher education sector. The value proposition of the college degree, long the most guaranteed route to professional preparation for work, is no longer keeping pace with rapidly evolving skill needs that derive from technological advancements impacting today's work force. If the university system does not engage in responsive restructuring, more and more workplaces will bypass them entirely and, instead, identify alternative sources of training that equip learners with competencies to directly meet dynamic needs. The College Devaluation Crisis makes the case that employers and other learning and development entities are emerging to innovate new approaches to training talent that, at times, relies on the higher education sector, but increasingly operates independently in order to satisfy talent needs more agilely and effectively. Written primarily for managers, the book focuses on case studies from leading companies, including Google, Ernst & Young, IBM, and Marriott, to illustrate their innovative strategies for talent development across varying levels of individual education, age, and background. The book also addresses professionals on the university side, urging readers to consider the question: Will higher education pivot and adapt, or will it resist change and, therefore, be replaced?"--